2019
DOI: 10.1016/j.isci.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Nanosheet of Graphdiyne-Supported Palladium Atom Catalyst for Efficient Hydrogen Production

Abstract: SummaryAtomic catalysts are promising alternatives to bulk catalysts for the hydrogen evolution reaction (HER), because of their high atomic efficiencies, catalytic activities, and selectivities. Here, we report the ultrathin nanosheet of graphdiyne (GDY)-supported zero-valent palladium atoms and its direct application as a three-dimensional flexible hydrogen-evolving cathode. Our theoretical and experimental findings verified the successful anchoring of Pd0 to GDY and the excellent catalytic performance of Pd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 159 publications
(133 citation statements)
references
References 53 publications
1
126
0
Order By: Relevance
“…Pd 1 /GDY/G, Pd 1 /GDY/G‐1, and Pd 1 /GDY/G‐2 with 0.855, 0.151, and 0.272 wt% Pd were prepared, respectively. The content of Pd in Pd 1 /GDY/G is about fourfold higher than previously reported Pd SAC supported by GDY nanosheets . Pd 1 /GDY/G exhibits excellent catalytic activity and high turnover frequency (TOF, defined here as the amount of reactant that is converted into product per min by 1 mmol of Pd) compared with previously reported Pd‐based catalysts, including the Pd SAC.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Pd 1 /GDY/G, Pd 1 /GDY/G‐1, and Pd 1 /GDY/G‐2 with 0.855, 0.151, and 0.272 wt% Pd were prepared, respectively. The content of Pd in Pd 1 /GDY/G is about fourfold higher than previously reported Pd SAC supported by GDY nanosheets . Pd 1 /GDY/G exhibits excellent catalytic activity and high turnover frequency (TOF, defined here as the amount of reactant that is converted into product per min by 1 mmol of Pd) compared with previously reported Pd‐based catalysts, including the Pd SAC.…”
Section: Introductionmentioning
confidence: 66%
“…The valence states of Pd/GDY/G‐O and Pd 1 /GDY/G were investigated by XPS (Figure S17, Supporting Information). As shown in Figure e, the peaks of Pd 3d 5/2 and 3d 3/2 in Pd 1 /GDY/G shift to lower binding energy (335.2 and 340.8 eV) compared to those of Pd 1 /GDY/G‐O (337.4 and 342.7 eV), indicating the formation of zero‐valent palladium (Pd 0 ) complexes . The atomic‐resolution HAADF‐STEM image of Pd 1 /GDY/G illustrated that Pd atoms on the Pd 1 /GDY/G still maintain atomically dispersion without presence of any visible clusters or nanoparticles (NPs) (Figure S18, Supporting Information).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Very recently, Xue's group successfully stabilized zero‐valence palladium atoms (Pd 0 ) on GDY surface through electrochemical deposition, which displayed superior HER performance. [ 113 ] The authors investigated the critical mechanism of superior HER performance through their proposed two‐way crossover linear response technique. [ 114 ] The result showed that both singly and triply symmetrically fixed Pd atoms held the closed shell (crossover) effect, which manifested the formidable orbital overlaps between Pd atoms and adjacent C atoms.…”
Section: Gdy Supported Electrocatalysts For Energy Conversionmentioning
confidence: 99%